2009
DOI: 10.1155/2009/329632
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Ultrastructural Analysis of Cerebral Cortex, Cerebellum, and Hypothalamus from Diabetic Rats

Abstract: Autonomic and peripheral neuropathies are well-described complications in diabetes. Diabetes mellitus is also associated to central nervous system damage. This little-known complication is characterized by impairment of brain functions and electrophysiological changes associated with neurochemical and structural abnormalities. The purpose of this study was to investigate brain structural and ultrastructural changes in rats with streptozotocin-induced diabetes. Cerebral cortex, hypothalamus, and cerebellum were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

16
77
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(94 citation statements)
references
References 46 publications
(40 reference statements)
16
77
1
Order By: Relevance
“…The myelin-like figures that appeared in the cytoplasm of the Purkinje cells in the current study agree with the findings observed in the neuronal body of the cerebellum in diabetic rats, which has been attributed to degenerated mitochondria [23].…”
Section: Discussionsupporting
confidence: 92%
“…The myelin-like figures that appeared in the cytoplasm of the Purkinje cells in the current study agree with the findings observed in the neuronal body of the cerebellum in diabetic rats, which has been attributed to degenerated mitochondria [23].…”
Section: Discussionsupporting
confidence: 92%
“…Severe neuropathy causes thickening of axons, decreased microfi laments and capillary narrowing, which will lead to weakness and unbalanced walking (Tripathi and Srivastava, 2006).Structural and ultra-structural changes in the form of disarrangement of myelin sheath, degenerative changes of neurons and glia, presynaptic vesicle dispersion in swollen axonal bouttons, fragmentation of neurofi laments and oligodendrocyte abnormalities were observed in the cerebral cortex of streptozotocin (STZ) induced diabetic rats (Hernandez-Fonseca et al, 2009). …”
mentioning
confidence: 99%
“…Expanded perivascular space and perivascular swelling is similar to those observed in diabetic rats and could represent swollen pericytes, astrocytes, or adipocytes leading to disruption of the blood brain barrier (BBB) functions [41]. The generation of reactive oxygen species, in particular superoxide is thought to be a major factor in cholesterol's effects on dysfunction of the microvasculature [42].…”
Section: Discussionmentioning
confidence: 92%